Student Management in Enhancing Discipline at Excellent Madrasah Aliyah (Islamic Senior High School) - Khumairoh, Hilma Shinta Nafilatul; Zaini, Zainuddin Al Haj; Usriyah, Lailatul (Electronic Journal of Education, Social Economics and Technology, 2025)
This study examines a critical issue concerning student management in fostering discipline among students at Excellent Madrasah Aliyah (Islamic Senior High School) NURIS Jember. Students represent a nation's most valuable asset in ensuring a high-quality future. The primary objective of this research is to investigate how student management can be effectively implemented to enhance student discipline at Madrasah Aliyah Nuris Jember. This study employs field research utilizing a qualitative approach, producing descriptive data. The findings suggest that key factors such as punctuality, consistency in daily routines, proper uniform maintenance and hygiene, effective communication regarding attendance, compliance with assigned tasks, responsibility in classroom duties, participation in extracurricular activities, and efficient time management collectively contribute to shaping students’ character.